Altered balance of excitatory and inhibitory learning in a genetically modified mouse model of glutamatergic dysfunction relevant to schizophrenia - David J. Sanderson (Nature Portfolio, 2017)
Abstract The GluA1 AMPAR subunit (encoded by the Gria1 gene) has been implicated in schizophrenia. Gria1 knockout in mice results in recently experienced stimuli acquiring aberrantly high salience. This suggests that GluA1 may be important for learning that is sensitive to the temporal contiguity between events. To test this, mice were trained on a Pavlovian trace conditioning procedure in which the presentation of an auditory cue and food were separated by a temporal interval. Wild-type mice initially learnt, but with prolonged training came to withhold responding during the trace-conditioned cue, responding less than for another cue that was nonreinforced. Gria1 knockout mice, in contrast, showed sustained performance over training, responding more to the trace-conditioned cue than the nonreinforced cue. Therefore, the trace-conditioned cue acquired inhibitory properties (signalling the absence of food) in wild-type mice, but Gria1 deletion impaired the acquisition of inhibition, thus maintaining the stimulus as an excitatory predictor of food. Furthermore, when there was no trace both groups showed successful learning. These results suggest that cognitive abnormalities in disorders like schizophrenia in which gluatamatergic signalling is implicated may be caused by aberrant salience leading to a change in the nature of the information that is encoded.